Wschód porwany? Obraz westernizującej się Polski w eseistyce Wiktora Jerofiejewa i Andrzeja Stasiuka - Stryjakowska, Anna (Acta Polono-Ruthenica, 2018)
The article is an attempt of comparative analysis of selected essays by Victor Erofeev and Andrzej Stasiuk. One of the factors uniting their work is the vision of Central-Eastern Europe as a region which has been losing its genuineness due to the expansion of the Western liberal democracy. In this context the uniting Europe turns out to be a dehumanised space of forced coexistence, having reached a deadlock owing to the hypertrophy of political correctness. In the outlined circumstances Poland seems to be fully content with the role of peripheral consumer of the gains of late capitalism. Meanwhile Russia manages to save a distinctive identity and is thus becoming an appropriate viewpoint on the westernized countries of „the new Europe”. An integral part of the proposed analysis is a critical assessment of the writers’ narrative strategies, that prove a deep connection to the own culture and an inability to completely overcome (auto)stereotypes reproduced by this culture.